If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -16) = 12x Reorder the terms: 8(-16 + x) = 12x (-16 * 8 + x * 8) = 12x (-128 + 8x) = 12x Solving -128 + 8x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -128 + 8x + -12x = 12x + -12x Combine like terms: 8x + -12x = -4x -128 + -4x = 12x + -12x Combine like terms: 12x + -12x = 0 -128 + -4x = 0 Add '128' to each side of the equation. -128 + 128 + -4x = 0 + 128 Combine like terms: -128 + 128 = 0 0 + -4x = 0 + 128 -4x = 0 + 128 Combine like terms: 0 + 128 = 128 -4x = 128 Divide each side by '-4'. x = -32 Simplifying x = -32
| -2(3y-4)-y=2(y-5) | | 22/5x | | 2.75=2400+1175x | | (x-2)2+(y-0)2=64 | | 2(x-18)=-3(x+10) | | 2.75=4200+1175x | | X-81=261 | | -x-4x-7y=12 | | 3y^2+25y-28=0 | | -0.25x^3+3x+5=0 | | 4(x-5)=-8+x+19 | | 2L-15=8 | | -x-4x-0y=12 | | 4-8(-2-6t)ift=1 | | 5-6h=-5 | | 15+3b=-6 | | 7-s=-4 | | 45=-3x+3 | | -9(8-2x)=-10 | | 4t-7=-4 | | 6p-18/2=7 | | n-30/3=6 | | 3x=-2y+6 | | n-30/3 | | 6p-18/2 | | 6a+a^2-a=0 | | x^2-6x+19=16 | | .25+x=2000 | | 40=2(10-5x) | | 9(c-3)=6 | | (4a+3)(3a-1)= | | 3x+4(12)=117 |